EFFECT OF WARM WATER COMPRESS THERAPY ON THE INCIDENCE OF HYPEREMIA IN PHLEBITIS PATIENTS AT THE INPATIENT WARD OF BRIGJEND H. HASAN BASRI GENERAL HOSPITAL KANDANGAN - Nurul Hidayah; Topan Aditya Rahman; Desilestia Dwi Salmarini (Fakultas Kedokteran Universitas Lambung Mangkurat, 2017)
Abstract: This study aims to determine the effect of warm water compress therapy on the incidence of hyperemia in 40 patients with phlebitis at the Inpatient Installation of H. Hasan Basry General Hospital Kandangan. Research method used quasi-experimental with two group; control and intervention. The control group was untreated phlebitis, while the intervention group was a phlebitis patient treated with warm water compresses. Data collection was collected by measuring the redness diameter before and after warm compress therapy. The result showed that the mean of intervention group diameter before treatment 49.3 mm and after treatment 40.2 mm. The mean diameter of control group before treatment 48.1 mm and after treatment 46.4 mm. The mean diameter of intervention group was decreased 9.1 mm and 1.7 mm in the control group. Statistically result test show that there was a significant difference of mean hyperemia diameter between intervention and control group (p<0.05). Statistically result test also shows that there was a significant difference of mean hyperemia between pre- and post-treatment with warm water (p<0.05). It was concluded that the warm compress therapy could decreased the incidence of hyperemia in phlebitis patients. Keywords: Hyperemia, Phlebitis, Warm Compress Therapy